2019
DOI: 10.2174/1871527317666181004155136
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics in Neurodegenerative Diseases: The Role of Histone Deacetylases

Abstract: Background & Objective: Imbalance in histone acetylation levels and consequently the dysfunction in transcription are associated with a wide variety of neurodegenerative diseases. Histone proteins acetylation and deacetylation is carried out by two opposite acting enzymes, histone acetyltransferases and histone deacetylases (HDACs), respectively. In-vitro and in-vivo animal models of neurodegenerative diseases and post mortem brains of patients have been reported overexpressed level of HDACs. In recent pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 70 publications
0
31
0
Order By: Relevance
“…Their results highlighted the role of the epigenome in pathological disruptions of the neural circuits [27]. Additionally, the imbalance in histone acetylation levels and consequently the dysfunction in transcription have been associated with a wide variety of NDDs [28]. In vitro and in vivo animal models and post-mortem analysis of brains derived from NDDs patients reported overexpressed level of histone deacetylases (HDACs), thus encouraging new therapeutic approaches in this direction [29][30][31].…”
Section: Mirnas As Pharmacoepigenomic Targets For Nddsmentioning
confidence: 99%
“…Their results highlighted the role of the epigenome in pathological disruptions of the neural circuits [27]. Additionally, the imbalance in histone acetylation levels and consequently the dysfunction in transcription have been associated with a wide variety of NDDs [28]. In vitro and in vivo animal models and post-mortem analysis of brains derived from NDDs patients reported overexpressed level of histone deacetylases (HDACs), thus encouraging new therapeutic approaches in this direction [29][30][31].…”
Section: Mirnas As Pharmacoepigenomic Targets For Nddsmentioning
confidence: 99%
“…The work developed by Hu et al 173 reports the development of new HDAC6 selective inhibitors based on the structure of the antioxidant small molecule ebselen (28). The study was carried out through the evaluation of several linkers to incorporate the hydroxamic acid group in the structure of ebselen (28), in which the benziso-selenazol-3(2H)-one moiety could serve as a cap group. As a consequence, they discovered analog 29, a far more potent HDAC6 inhibitor (IC 50 = 0.037 µM) than its precursor (IC 50 = 11.5 µM) ( Figure 15).…”
Section: Hdacis As a Starting Point To Design Mtdls For Ndsmentioning
confidence: 99%
“…173 Additionally, the authors evaluated the free oxygen radical scavenging ability of 29 (ORAC-FL = 2.2), which was superior to that displayed by ebselen (28) (ORAC-FL = 0.7), and its glutathione peroxidase-like activity using different peroxides, which was quite similar to that of the reference compound. Cellular evaluations of the protective effect of 29 on H 2 O 2 -induced PC12 cell damage indicated that the protective effect of this compound is more potent than that of ebselen (28) alone or when the HDAC6 selective inhibitor tubastatin A (HDAC6 IC 50 = 0.020 µM) was used. 173 GSK-3β is considered a very promising target in AD-related diseases with the modulation of tau phosphorylation.…”
Section: Hdacis As a Starting Point To Design Mtdls For Ndsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then a large number of studies have demonstrated the ability of structurally distinct HDAC inhibitors to protect in diverse cell culture, invertebrate, and mammalian models of neurodegenerative conditions. 17,3840 However, because these pharmacological inhibitors are generally non-selective with respect to the HDAC family, the identity of the specific HDAC(s) that trigger neurodegeneration and that are targeted by the inhibitors to afford protection has been unresolved. A growing and compelling body of evidence points to HDAC3 being a particularly important player in the promotion of neurodegeneration in a variety of disease models.…”
Section: Hdac3 As a Key Contributor To Neurodegenerative Diseasementioning
confidence: 99%